2021
DOI: 10.1155/2021/6676107
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Derived Exosomal hsa-miR-4488 and hsa-miR-1228-5p: Novel Biomarkers for Dermatomyositis-Associated Interstitial Lung Disease with Anti-Melanoma Differentiation-Associated Protein 5 Antibody-Positive Subset

Abstract: The present study is aimed at profiling circulating exosome-derived microRNAs (miRNAs/miRs) from patients with dermatomyositis (DM), in particular those complicated with interstitial lung disease (ILD) with anti-melanoma differentiation-associated protein 5 (MDA5) antibody-positive. Fifteen participants were enrolled, including five patients with DM complicated with ILDs prior to treatment with circulating anti-MDA5 antibody-positive status [DM-ILD-MDA5 Ab(+)], five DM patients without ILDs who were negative f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…However, tRF-28-QSZ34KRQ590K did not show any significant correlation with the disease severity of atopic dermatitis. Another autoimmune condition was examined by Zhong et al [ 74 ], where the exosomal RNA profile from the blood samples of 10 dermatomyositis patients, with half of the patients having simultaneous interstitial lung disease (ILD) involvement, was investigated. In all three patient groups, namely dermatomyositis patients with ILD and without ILD and control patients, exosomal tRNA represented one of the smallest proportions of sRNA, with 0.42%, 0.49% and 0.64%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, tRF-28-QSZ34KRQ590K did not show any significant correlation with the disease severity of atopic dermatitis. Another autoimmune condition was examined by Zhong et al [ 74 ], where the exosomal RNA profile from the blood samples of 10 dermatomyositis patients, with half of the patients having simultaneous interstitial lung disease (ILD) involvement, was investigated. In all three patient groups, namely dermatomyositis patients with ILD and without ILD and control patients, exosomal tRNA represented one of the smallest proportions of sRNA, with 0.42%, 0.49% and 0.64%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, biomarkers or therapeutic targets in BPD diagnostics and prediction appear to be particularly important ( 40 ). MiRNAs have been extremely studied in many diseases due to their utility in diagnostics of oncology ( 41 ), infectious diseases ( 42 ), and lung disease ( 43 ). Previous research found that miR34a was considerably increased in the lungs of mice subjected to hyperoxia compared to normal controls, but decreased when exposed to hypoxia ( 35 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal microRNAs (miRNAs) stably circulate in the blood and are biomarkers for various diseases. A study showed that upregulated plasma‐derived exosomal miR‐4488 and miR‐1228‐5p might help diagnose, prevent, and treat MDA5 + DM‐ILD based on next‐generation sequencing 96 . Besides miRNA, high serum levels of cell‐free DNA (cfDNA), mainly produced by neutrophil extracellular traps (NETs), may reflect NETs involved in MDA5 + DM‐ILD pathogenesis 97 .…”
Section: Blood‐based Molecular Biomarkers In Mda5+dm‐ildmentioning
confidence: 99%
“…A study showed that upregulated plasma‐derived exosomal miR‐4488 and miR‐1228‐5p might help diagnose, prevent, and treat MDA5 + DM‐ILD based on next‐generation sequencing. 96 Besides miRNA, high serum levels of cell‐free DNA (cfDNA), mainly produced by neutrophil extracellular traps (NETs), may reflect NETs involved in MDA5 + DM‐ILD pathogenesis. 97 Circulating NET [both human neutrophil elastase (HNE)‐DNA and myeloperoxidase (MPO)‐DNA complexes] are elevated in MDA5 + DM patients, suggesting that anti‐MDA5 antibodies may enhance NET formation, reflecting neutrophil dysregulation.…”
Section: Blood‐based Molecular Biomarkers In Mda5 ...mentioning
confidence: 99%